BCOOPL: Basic concurrent object-oriented programming language - de Bruin, Hans (Software, practice & experience, 2000)
A small, object‐oriented language is introduced: BCOOPL (Basic Concurrent Object‐Oriented Programming Language). This language is specifically targeted to support component‐oriented programming. The main design goal of BCOOPL was to provide a small, but powerful set of language features that supports the construction of high‐quality components through well‐established software engineering practices, which include the separation of interfaces and implementations, weakly‐coupled objects, and ion. A number of design patterns based on these principles is actually built in the language. In particular, the observer, the mediator and the bridge are supported directly. This provides a strong foundation on which higher level component specification languages can be built. BCOOPL has a long research history. Its roots can be traced back to path expressions, and the concurrent object‐oriented programming languages Procol and Talktalk. As a result, BCOOPL only integrates essential language features that blend well and have proven their value in practice. Copyright © 2000 John Wiley & Sons, Ltd.